2011
DOI: 10.1111/j.1526-100x.2009.00524.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant and Soil Responses to Created Microtopography and Soil Treatments in Bottomland Hardwood Forest Restoration

Abstract: Although microtopographic heterogeneity is common in bottomland hardwood forests, it is rarely considered in bottomland restoration efforts. The objective of this study was to determine the responses of hydrologic condition, soil physiochemical properties, and introduced and colonizing vegetation to created microtopography and soil treatments at a landfill borrow pit in northern Texas. A series of mounds and pools were created and planted with fast-growing pioneer species as well as more desirable, later-succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 39 publications
3
30
0
Order By: Relevance
“…However, this limits the site to a single water table depth, which can limit species diversity and create a greater risk of mortality of planted seedlings from seasonal high water. Research of Bruland and Richardson (2005) and Simmons et al (2011) have highlighted the importance of topographic heterogeneity in restored bottomland hardwood forests in the southern United States. Our results suggest that the same may be true for northern white-cedar wetlands.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this limits the site to a single water table depth, which can limit species diversity and create a greater risk of mortality of planted seedlings from seasonal high water. Research of Bruland and Richardson (2005) and Simmons et al (2011) have highlighted the importance of topographic heterogeneity in restored bottomland hardwood forests in the southern United States. Our results suggest that the same may be true for northern white-cedar wetlands.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, elevated microtopography could be an important component in natural regeneration of northern white-cedar in wetlands, especially during the critical stages of germination and seedling establishment. Previous studies investigating the effects of artificially-created microtopography on tree growth and survival have primarily taken place in bottomland hardwood swamps, which have shown that the drier conditions of hummock tops and ridges increase performance and survival of certain tree species (Simmons et al 2011(Simmons et al , 2012. Studies involving microtopography in northern whitecedar wetlands have been of natural systems, where microtopography is primarily composed of organic material (Chimner and Hart 1996).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, given the practical limitations related to sampling strategies in both the ecosite classification process and this study, it is difficult to characterize fine scale variability. For example, Simmons et al [33] found in a study of bottomland forests that microtopography at scales of decimeters or less affected hydrologic conditions, nutrient concentrations, and species composition. Microbial communities, another important control on many soil processes, also vary substantially at fine scales; Snajdr et al [34] assessed the spatial variability of enzyme activities and microbial biomass in upland hardwood forest soils and found significant differences between samples taken only 1 cm apart.…”
Section: Resultsmentioning
confidence: 99%